Unearthing unevenness of potato seed networks in the high Andes: a comparison of distinct cultivar groups and farmer types following seasons with and without acute stress - Arce, Alejandra; Haan, Stef de; Burra, Dharani Dhar; Ccanto, Raul I. (International Center for Tropical Agriculture, 2018)
The purpose of the research was to understand the fine-grained dynamics underlying potato seed networks in a center of crop origin and biodiversity, the central Andes of Peru, by differentiating between seasons with and without acute stress (i.e. frost, late blight), cultivar groups, and farmer types. Cultivar groups were classified into (i) bred varieties, (ii) commercial floury landraces, (iii) non-commercial floury landraces (single cultivars), (iv) non-commercial floury landraces (mixed cultivars), and (v) bitter landraces. Farmer types were classified as (i) general farmers, (ii) seed specialists, and (iii) custodian farmers. We documented seed provisions and acquisitions through the application of a semi-structured survey to 336 households in 2014-2015 in two main regions of the Peruvian central Andes: Huancavelica and Pasco-Junin. Farmers self-determined the most recent seasons with and without acute stress, specified the cause of the stress (i.e. frost, hail, late blight, drought), and described seed transactions for each season. The survey consisted of ten sections: (i) socioeconomic data; (ii) cropping season; iii) cultivar-level procurement; iv) seed volumes; v) specific seed sources and sinks; vi) social relationship to providers and clients; vii) seed transaction types; viii) place (s) of seed transaction; ix) seed destination/origin; x) quality guarantee of seed (including certification). For each respondent, every single transaction of seed acquisition and provision was recorded as a separate entry. Results confirm that seed networks are uneven and distinct for cultivar groups and farmer types. The study details the adaptations the system makes in the aftermath of acute stress and assesses the implications of its dynamics for conservation. Seed networks did re-organize following seasons with acute seed stress. A notable shift involved a contraction of seed networks within sub-regional clusters. Following stress, the directionality of seed provision versus acquisition inverts. We conclude that the self-regulatory capacity of farmer seed networks represents a strong safety net through which smallholders can respond to crop failure and seed stress. (2014-10)